Dynamic Sorting of Nuclear Components into Distinct Nucleolar Caps during Transcriptional Inhibition - Shav-Tal, Yaron (The American Society for Cell Biology, 2005)
Nucleolar segregation is observed under some physiological conditions of transcriptional arrest. This process can be mimicked by transcriptional arrest after actinomycin D treatment leading to the segregation of nucleolar components and the formation of unique structures termed nucleolar caps surrounding a central body. These nucleolar caps have been proposed to arise from the segregation of nucleolar components. We show that contrary to prevailing notion, a group of nucleoplasmic proteins, mostly RNA binding proteins, relocalized from the nucleoplasm to a specific nucleolar cap during transcriptional inhibition. For instance, an exclusively nucleoplasmic protein, the splicing factor PSF, localized to nucleolar caps under these conditions. This structure also contained pre-rRNA transcripts, but other caps contained either nucleolar proteins, PML, or Cajal body proteins and in addition nucleolar or Cajal body RNAs. In contrast to the capping of the nucleoplasmic components, nucleolar granular component proteins dispersed into the nucleoplasm, although at least two (p14/ARF and MRP RNA) were retained in the central body. The nucleolar caps are dynamic structures as determined using photobleaching and require energy for their formation. These findings demonstrate that the process of nucleolar segregation and capping involves energy-dependent repositioning of nuclear proteins and RNAs and emphasize the dynamic characteristics of nuclear domain formation in response to cellular stress.